1971
DOI: 10.1111/j.1365-2133.1971.tb14197.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mycosis Fungoides Cell: The Skin Window in Mycosis Fungoides

Abstract: SUMMARY.— The skin‐window technique was applied to normal und involved skin sites of 17 patients with mycosis fungoides, 8 patients with parapsoriasis en plaque, and 6 patients with cutaneous lymphomata, and also to normal skin of 25 controls. Large mononuclear cells rapidly migrated in large numbers from plaques of mycosis fungoides and parapsoriasis. Identical cells were seen in skin windows from control sites at later intervals. No malignant cells were found in any of the skin windows of mycosis fungoides o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1973
1973
1984
1984

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Similar cells have been seen with the light microscope (Flaxman, Zelazny & Van Scott, 1971) and with the electron microscope (Lutzner et al, 197I5 and Flaxman et al, 1971) in benign non-lymphomatous conditions. Vesper, Winkelmann & Hargraves (1971), using the skin window technique, considered they were benign primitive cells with no features of malignancy. Bellanti & Green (1971) considered immunological reactivity as an expression of efficiency in the elimination of foreigness.…”
Section: Discussionmentioning
confidence: 99%
“…Similar cells have been seen with the light microscope (Flaxman, Zelazny & Van Scott, 1971) and with the electron microscope (Lutzner et al, 197I5 and Flaxman et al, 1971) in benign non-lymphomatous conditions. Vesper, Winkelmann & Hargraves (1971), using the skin window technique, considered they were benign primitive cells with no features of malignancy. Bellanti & Green (1971) considered immunological reactivity as an expression of efficiency in the elimination of foreigness.…”
Section: Discussionmentioning
confidence: 99%
“…Lutzner et al (1971) have seen it with the electron microscope in lichen planus and morphologically identical cells have been detected by Flaxman et al (1971) in a variety of non-lymphomatous dermatoses. Vesper, Winkelmann & Hargraves (1971), using the skin window technique, have found that the same cells migrate from normal skin as from mycosis fungoides, and on the basis of their light microscope appearance have proposed that they are benign immature reticular cells lying somewhere between a reticulum cell and a histiocyte.…”
Section: Discussionmentioning
confidence: 99%
“…In the first class of investigations falls Ascheim's study of skin windows put on involved and uninvolved psoriatic skin (Ascheim et al, 1966). Another is Vesper's study of subjects with mycosis fungoides, where diseased skin is compared to the '... contralateral normal skin...' (Vesper et al, 1971). The psoriasis study revealed no mean differences in percentages of cell types at various hours; on the other hand, in the early hours of inflammation the mycosis fungoides plaques were noted to have higher median percentages of mononuclear cells than uninvolved skin.…”
Section: Arms)mentioning
confidence: 99%
“…The skin window technique is a method of recording the cellular events occurring at the skin's surface at timed intervals following an initial stimulus. It has been used to study the cell types involved in various inflammatory and neoplastic states (Ascheim et al, 1966;Eidinger, Wilkinson & Rose, 1964;Fowler & Lowell, 1966;Garrie & Wolf-Jurgensen, 1971;Hautklin, 1968;Vesper, Winkelman & Hargraves, 1971;Wolf-Jurgensen, 1962Wolf-Jurgensen, Hermingsen & Zachariae, 1969;Wolf-Jurgensen & Zachariae, 1965).…”
mentioning
confidence: 99%